2022
DOI: 10.1177/15353702221090454
|View full text |Cite
|
Sign up to set email alerts
|

Hyperinflammation, apoptosis, and organ damage

Abstract: The cytokine storm (CS) in hyperinflammation is characterized by high levels of cytokines, extreme activation of innate as well as adaptive immune cells and initiation of apoptosis. High levels of apoptotic cells overwhelm the proper recognition and removal system of these cells. Phosphatidylserine on the apoptotic cell surface, which normally provides a recognition signal for removal, becomes a target for hemostatic proteins and secretory phospholipase A2. The dysregulation of these normal pathways in hemosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 154 publications
1
8
0
Order By: Relevance
“…Previous studies have shown that oxidative stress ultimately leads to apoptosis of neuronal cells . The cysteine protease family is the primary regulator of apoptosis. , The caspase-3 apoptosis pathway plays a key role in apoptosis . In the present study, immunofluorescence and Tunel assays showed that SeNPs-Met-MVs could significantly reduce the expression of apoptotic factors (cleaved caspase-3).…”
Section: Discussionsupporting
confidence: 59%
“…Previous studies have shown that oxidative stress ultimately leads to apoptosis of neuronal cells . The cysteine protease family is the primary regulator of apoptosis. , The caspase-3 apoptosis pathway plays a key role in apoptosis . In the present study, immunofluorescence and Tunel assays showed that SeNPs-Met-MVs could significantly reduce the expression of apoptotic factors (cleaved caspase-3).…”
Section: Discussionsupporting
confidence: 59%
“…Oxidative stress and inflammation are important triggers of gastric ulcers [ 26 ]. Proinflammatory factors such as IL-1β, IL-6, TNF-α, and PEG2 play a crucial role in the inflammatory response [ 27 ]. TNF-α stimulates IL-1β production and cell apoptosis, leading to delayed ulcer healing [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…A dysregulated inflammatory response can have several causes: excessively high pathogen load in the context of sepsis, inadequate sensing or triggering of the immune system without the presence of a pathogen at all (as occurs with Castleman’s disease), or inappropriate inflammasome activation due to genetic disease [ 36 , 37 , 38 ]. Further examples are the inability of the immune system to terminate an initially adequate immune response and return to baseline (e.g., primary hemophagocytic lymphohistiocytosis, HLH) or conditions with uncontrolled infection and persistent immune activation (e.g., macrophage activation syndrome (MAS)-HLH in, e.g., CMV, EBV, or Influenza) [ 39 ].…”
Section: Pathophysiology Of Csmentioning
confidence: 99%